HIBRIDITY OF TRADITION: PESANTREN'S EPISTEMOLOGICAL RESOLUTION IN NAVIGATING THE REGIME OF DIGITALIZATION - Nana Fitriana; Muhammad Musip; Lalu Muh. Sulhan Zihadi; Mustamin Hafifi; Yus’an; Asbullah Muslim; Babun Suharto (UIN Mataram, 2026)
The rapid advancement of digitalization has significantly transformed the landscape of education, including traditional Islamic boarding schools (pesantren). This study aims to examine how pesantren negotiate epistemological tensions between tradition and emerging digital knowledge systems. Using a qualitative-descriptive approach based on library research, this paper argues that pesantren develop a hybrid epistemology by integrating classical Islamic scholarship (turāth) with digital learning practices. The concept of hybridity enables pesantren to maintain their identity while adapting to contemporary technological demands. The findings indicate that pesantren construct their epistemological resolution through selective adoption, cultural filtering, and contextual reinterpretation of digital knowledge. This hybrid model positions pesantren as resilient educational institutions capable of navigating the regime of digitalization without losing their foundational religious values